Quality Education in Practice: How Muhammadiyah's Role in Realizing SDG-4 in Kendari - Yusuf; Muallimah; Asman (Mimbar Agama Budaya, 2025)
This research is motivated by the existing disparities in access to and quality of Islamic education in Kendari City. In this context, the establishment of Muhammadiyah educational institutions becomes crucial to support the achievement of Sustainable Development Goal 4 (Quality Education). This study employs a descriptive qualitative design, with research sites located in several Muhammadiyah schools and madrasahs in Kendari City. The participants include school principals, teachers, administrators of the Muhammadiyah regional boards, and students. Data were collected through interviews, observations, and documentation. The findings reveal that the existence of Muhammadiyah in the field of Islamic education in Kendari contributes to the realization of SDG 4 on Quality Education through four key aspects: (1) the establishment of educational institutions, (2) the improvement of community education, (3) the promotion of moderate and progressive Islamic education through inclusive Muhammadiyah schools, and (4) the integration of Muhammadiyah education with the objectives of SDG 4. This suggests that strengthening the quality of Muhammadiyah education in Kendari requires a collaborative approach involving the organization, the government, and the community. Such collaboration should be accompanied by innovations in financing, management, and human resource development to ensure the sustainable achievement of the goals of providing equitable and high-quality Islamic education.